EFFECT OF LIQUIDITY, SOLVENCY, PROFITABILITY AND ACTIVITY REGARDING STOCK RETURNS - I Kadek Yoga Dwiantara; Sayu Ketut Sutrisna Dewi (Adisam Publisher, 2024)
Returnshares are the value obtained as a result of investment activities. Return is very important as an attraction for investors to invest their investment funds. The aim of this research is to analyze and explain the influence of liquidity, solvency, profitability and activity on stock returns. The number of samples in this study was 23 companies included in the LQ45 index on the Indonesia Stock Exchange for the 2020-2023 period. Data collection uses non-participant observation methods. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that liquidity has a significant positive effect on stock returns, solvency has an insignificant negative effect on stock returns, profitability has a significant positive effect on stock returns, and activity has an insignificant positive effect on stock returns.